Weather based wheat yield prediction model for the state of Himachal Pradesh, India (Bangladesh Journal of Botany, 2025)
Yield forecast models of wheat for different districts of state have been prepared using long term crop yield data as well as weather data from 48th week to 11th standard meteorological week for respective districts. The data from the period of (1990-2020) has been used in developing the forecast model and the remaining two years data from (2021-2022) has been used for the validation of the models. Model performance was evaluated by calculating the different statistical parameters viz. Standard Error (SE), Correlation Coefficient and Root Mean Square Error (RMSE). According to R2 value the performance of the model in predicting yields at district level was quite satisfactory for all the districts. The percentage deviation between the observed and simulated yield ranged between acceptable limit i.e. ±10%. The model is simple and can be used for predicting the wheat yield at district, agro climatic zone and state level.Bangladesh J. Bot. 54(3): 587-592, 2025 (September)